Pengaruh Kepuasan Pelanggan terhadap Pelayanan di Kantor Honda Tunas Dwipa Matra Sengkang - Patotorijal Patotorijal; Yusran Yusran; Asmanurhidayani (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2025)
The development of the Honda Tunas Dwipa Matra company is certainly inseparable from the form of service provided to its customers. This form of service will influence customer satisfaction which ultimately has an impact on increasing company revenue. Customer satisfaction is an important factor in efforts to facilitate sales and purchases, this cannot be separated from the level of service provided. Therefore, companies must think more carefully about the importance of customer satisfaction in providing customer service. It is now increasingly recognized that service quality and customer satisfaction are vital aspects in order to survive in business and win the competition. Viewed from the aspect of research data collection, this research is a type of quantitative research using a survey approach which aims to test the combination/influence of independent variables on the dependent variable, namely Customer Satisfaction with Services at the Honda Tunas Dwipa Matra Sengkang Office. Based on the results of research regarding the influence of customer satisfaction on service at the Honda Tunas Dwipa Matra Sengkang Office, it can be concluded as follows: 1) Satisfaction at the Honda Tunas Dwipa Matra Sengkang Office is in the very good category. 2) Service at the Honda Tunas Dwipa Matra Sengkang Office is in the very good category. 3) The results of data analysis show that the influence provided is positive and significant and the relationship provided is at a strong interval.